Digital Literacy Management to Increase Student Reading Interest at SMA Negeri 1 Banggai - Masrato Masrato; Ikhfan Haris; Arifin Suking (International Journal of Education, Culture, and Society, 2026)
The increasing use of digital technology by students has not been adequately oriented toward literacy activities, but is instead dominated by non-academic uses such as social media, digital entertainment, and online games. This study aims to describe: (1) the preparation of digital literacy initiatives to increase students’ reading interest; (2) strategies for implementing digital literacy to enhance students’ reading interest; (3) assessment practices for digital literacy in relation to reading interest at SMA Negeri 1 Banggai; and (4) the sustainability of the digital literacy program at SMA Negeri 1 Banggai. Employing a qualitative approach with a case study design, the research was conducted at SMA Negeri 1 Banggai using observation, interviews, and document analysis, with data processed through an interactive data analysis model. The findings show that: (1) digital literacy preparation begins with analyzing initial needs, formulating objectives and programs, providing facilities and infrastructure, organizing implementation, and planning teacher competency development; (2) digital literacy implementation strategies to foster reading interest include the use of digital media and reading resources that are more engaging, interactive, and easily accessible; (3) digital literacy assessment is conducted reflectively and continuously within learning activities; and (4) evaluation results are used as the basis for program improvement and strengthening, including expanding digital reading collections, regulating device use, and reinforcing support for digital literacy implementation in classrooms and the school library. The study concludes that well-managed digital literacy programs can systematically enhance students’ reading interest when supported by adequate preparation, thoughtful implementation strategies, continuous assessment, and sustained institutional commitment.